Implementasi Pendidikan Karakter Berbasis Panca Jiwa di Pesantren: Strategi dan Tantangan dalam Era Digital - Al Faruq, Umar; Arifuddin, Nur; Ma’arif, A. Samsul; Husniyah, Farihatul (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2025)
This study aims to describe the implementation and impact of the Panca Jiwa (Five Souls) values in shaping the character of students at Ihyaul Qur’an Nururrahman Islamic Boarding School, Malang Regency. Using a qualitative method with participatory observation, in-depth interviews, and documentation techniques, the research reveals that the values of sincerity (ikhlas), simplicity, independence, Islamic brotherhood (ukhuwah Islamiyah), and freedom of thought are integrally internalized into students’ daily activities, the educational curriculum, and social interactions within the pesantren. The findings show that sincerity and simplicity are nurtured through the habituation of daily worship; independence is reflected in self-management and personal responsibility; Islamic brotherhood develops through collective social activities; while freedom of thought is fostered through discussion methods and peer tutoring. The impact of these values is evident in the students’ increased discipline, sense of responsibility, social empathy, and spiritual growth. The integration of technology in the learning process also supports character development in a contemporary context. This study reinforces the theory of character education based on a socio-religious environment and demonstrates that the Panca Jiwa values are not merely normative doctrines, but are practiced as a way of life that holistically shapes students' personalities.